Review of the Book Entitled Persian Grammar based on the Autonomous Theory in Dependency Grammar - Masood Ghayoomi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The dependency grammar is one of the grammar formalisms that is originated according to the dependency relations of lexical elements in a sentence. This dependency is based on the valence of the lexicon; therefore, in this formalism the semantic representation of the words as valence is the backbone of the grammar. The current paper reviews the book entitled “Persian Grammar based on the Autonomous Theory in Dependency Grammar” according to three major contents. Firstly, the chapters of the book are briefly overviewed. Then, the book’s content is evaluated and analyzed and the weak and strong points of the book are studied from different perspectives. In this section, some suggestions are provided for the terminology and expressed concepts. Since dependency grammar does not belong to generative grammar, a comparison is made between the dependency and phrase structure grammar formalisms to understand the content better and to ease the mind of the reader with the generative grammar background about the basic concepts of the dependency grammar. At the end, suggestions are provided to extend the dependency grammar in the book.